Financial Management Drives Report Quality Amid Low Literacy and Fintech Use: Manajemen Keuangan Mendorong Kualitas Laporan di Tengah Rendahnya Literasi dan Penggunaan Fintech - Haniifah , Khairunnisa; Jhoansyah, Dicky; Danial, R. Deni Muhammad (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Micro, small, and medium enterprises (MSMEs) are vital to Indonesia's economy, particularly in the culinary sector. Specific Background: Despite their growth, many culinary MSMEs struggle with poor financial reporting due to limited financial skills and low digital adoption. Knowledge Gap: Prior studies show mixed results on the influence of financial literacy, financial technology (fintech), and financial management on financial reporting quality, and few focus on culinary MSMEs in Sukabumi. Aims: This study analyzes the impact of financial literacy, fintech, and financial management on the quality of financial reports among culinary MSMEs in Sukabumi City. Results: Using quantitative associative methods with 180 MSMEs, the findings show that financial literacy negatively affects report quality, fintech has no significant effect, while financial management has a strong positive and dominant influence. The regression model explains 48.1% of the variance. Novelty: Unlike existing studies, this research identifies financial management as a stronger determinant than literacy or fintech, and highlights the counterintuitive negative role of financial literacy. Implications: The results emphasize the need for targeted training in financial practices and effective use of digital tools, supporting policy and program development for MSME financial capacity building in local contexts.Highlight : Financial management is the most dominant factor improving report quality. Financial literacy negatively affects the quality of financial reports. Fintech usage is still limited among culinary MSMEs. Keywords : Financial Literacy, Financial Technology, Financial Management, Financial Report Quality, Culinary MSMEs